Applied mathematics for the managerial, life, and social sciences - Tan, S. T. (Soo Tang) (Cengage Learning Asia Pte Ltd, 2013)
A traditional book with a modern feel, market-leading APPLIED MATHEMATICS FOR THE MANAGERIAL, LIFE, AND SOCIAL SCIENCES, Sixth Edition, teaches by application and uses real-world examples to motivate students. It combines solid theory with innovative technology, includes a robust supplement package, and offers unmatched flexibility that caters to both traditional and modern practitioners. Accessible for majors and non-majors alike, the new Sixth Edition utilizes an intuitive approach that marries real-life instances to what would otherwise be abstract concepts. This is the focus of new and insightful Portfolios, which highlight the careers of real people and discuss how they use math in their professions. Numerous exercises ensure that students have a solid understanding of concepts before advancing to the next topic. By offering a powerful array of supplements such as Enhanced WebAssign®, the new Sixth Edition enables students to maximize their study time and succeed in class.